Injectable sustainable andrographolide-releasing hydrogel for long-lasting alleviation of osteoarthritis and regulation of chondrocyte autophagy via PRKCA/EGFR - Yang Chen; Peipei He; Siyi Tao; Jintao Zhong; Kai Jiang; Yuching Hsu; Guang Xia; Xinzhan Mao; Hongxun Sang; Ke Lu (Materials Today Bio, 2025)
Osteoarthritis is one of the most prevalent age-related joint diseases, with chondrocyte inflammation and autophagy dysregulation serving as pivotal pathogenesis factors. Andrographolide (AD), a phytochemical identified in Andrographis paniculata, exhibits anti-inflammatory properties and regulates autophagy to safeguard cells from damage. Nevertheless, the precise mechanism underlying the influence of AD on autophagy in osteoarthritis (OA) chondrocytes remains unelucidated. Concurrently, sustained efficacy of andrographolide typically necessitates prolonged administration, posing a challenge for its clinical application. We engineered an injectable 4-arm PEG-Mix-Hydrogel/PF system capable of encapsulating lipophilic drugs and achieving sustained release over a period of up to 24 days, substantially reducing the frequency of medication. Our findings indicate that andrographolide augments chondrocyte autophagy via the PRKCA/EGFR pathway and modulates chondrocyte inflammation as well as extracellular matrix degradation. Subsequent experimentation revealed that the injectable 4-arm PEG-Mix-Hydrogel/PF@AD (PHPF@AD) exhibited excellent biocompatibility with chondrocytes, possessed a rapid in-situ gelation time, and a single injection was sufficient to alleviate joint degeneration, abnormal gait, and weakened chondrocyte autophagy in OA mice, while ameliorating inflammation, matrix degradation, and apoptosis levels, and maintaining a certain degree of bone mass around the joints. In summary, this injectable hydrogel with spontaneous andrographolide release is anticipated to be a promising therapeutic modality for OA.